Evaluasi dan Rancangan Sistem Ventilasi Pada Lubang Tambang BMK-35 CV. Bara Mitra Kencana, Tanah Kuning, Desa Batu Tanjung, Kota Sawahlunto - Andi Asmunandar; Bambang Heriyadi (Departemen Teknik Pertambangan FT UNP, 2018)
In underground mining activities required mine ventilation, it use to include fresh air needed by miners. Methane gas explosion has occured in CV. Bara Mitra Kencana on Wednesday, March 29, 2017. The tunnel location of explosion is currently contiguous to the location of the mine plan progress (BMK-35) that following the direction of coal deployment that has the potential of methane gas hazards, cause of that a good ventilation system design is required to prevent the explosion. After the evaluation there was a difference quantity of air entering and exit air, the air inside is 6,66 m3/s and the quantity of air outside is 6,33 m3/s. This is caused by ripped of the duct at the air intake is much as 6 points. Air temperature at the mine pit BMK-35 increased temperature of 1oC every 100 m of mine progress. Based on the evaluation results, the use of fan/blower with a capacity of 200 m3/min with a system of ducts using continue system every space 100 meters progress of underground mine. Based on the calculation the amount of air requirement is 4,05 m3/s while the venting capacity of the forcing fan and the suction vent (exhaust fan) is 12,02 m3/s. Based ;on that, we can concluded the addition of exhaust fan on canopy 3 already suffice the air requirement to support mining operational activities. Installation of the exhaust fan is doing to anticipate the accumulation of high methane gas, as one of the ventilation functions is to dissolve and bring out impurities from the gases in the mining area, so as to achieve a condition that is eligible to prevent the occurrence of gas explosions in minesKeywords: Evaluation, Ventilation System, Underground Mine, Velocity of Air, Air Volume